Psychological effects of rapid weight loss and attitudes towards eating among professional jockeys - Caulfield, M. J.; Karageorghis, C. I. (Journal of Sports Sciences, 2008)
We examined the psychological effects of rapid weight loss among a sample of 41 professional jockeys (mean age 30.9 years, s = 7.0). Participants completed the Brunel Mood Scale (BRUMS) and the Eating Attitudes Test-26 (EAT-26) to establish the relationships between rapid weight loss, mood, and attitudes towards eating. These instruments were administered on three occasions: at the jockeys' minimal weight (achieved through rapid weight loss), their optimal riding weight (when they were not excessively restricting their weight and felt healthy), and their relaxed weight (when there were no forthcoming light rides or no rides at all). It was hypothesized that when riding at minimal weight, jockeys would record a more negative mood profile compared with scores recorded at optimal or relaxed weights. The same trend was expected for eating attitudes. These hypotheses were supported as jockeys reported significantly more negative mood profiles and eating attitudes at minimal weight. The EAT-26 scores indicated the presence of disordered attitudes towards eating at this weight. These results suggest that jockeys' endeavours to reach the minimum weight limit stipulated by governing bodies are likely to jeopardize their psychological well-being. Dialogue surrounding the appropriateness of current weight regulations is therefore encouraged.